Susceptible and protective HLA class 1 alleles against dengue fever and dengue hemorrhagic fever patients in a Malaysian population. - Appanna, R.; Ponnampalavanar, S.; Lum Chai See, L.; Sekaran, S. D. (Public Library of Science, 2010)
These are the first findings on genetic polymorphisms in our population and we conclude that: (1) In our total population, HLA-B*53 probably involve in disease susceptibility, while the HLA-A*03 and HLA-B*18 may confer protection from progression to severe disease; (2) In the Malay population, HLA-B*13 and B*18 are probably associated in disease susceptibility and protection, respectively. These results could furnish as a valuable predictive tool to identify ethnically different individuals at risk and/or protection from severe forms of DENV infection and would provide valuable informations for the design of future dengue vaccine.